DNA repair as a shared hallmark in cancer and ageing - Thomas L. Clarke; Raul Mostoslavsky (Molecular Oncology, 2022)
Increasing evidence demonstrates that DNA damage and genome instability play a crucial role in ageing. Mammalian cells have developed a wide range of complex and well‐orchestrated DNA repair pathways to respond to and resolve many different types of DNA lesions that occur from exogenous and endogenous sources. Defects in these repair pathways lead to accelerated or premature ageing syndromes and increase the likelihood of cancer development. Understanding the fundamental mechanisms of DNA repair will help develop novel strategies to treat ageing‐related diseases. Here, we revisit the processes involved in DNA damage repair and how these can contribute to diseases, including ageing and cancer. We also review recent mechanistic insights into DNA repair and discuss how these insights are being used to develop novel therapeutic strategies for treating human disease. We discuss the use of PARP inhibitors in the clinic for the treatment of breast and ovarian cancer and the challenges associated with acquired drug resistance. Finally, we discuss how DNA repair pathway‐targeted therapeutics are moving beyond PARP inhibition in the search for ever more innovative and efficacious cancer therapies.